Evaluation of low temperature tolerance in irrigated rice (Oryza sativa L.) genotypes at reproductive phase in a field experiment, during a spontaneous climatic event in the 2019/2020 crop season (Revista de Ciências Agroveterinárias, 2023)
Concerning the occurrence of a spontaneous event of low temperatures (
Keywords: microsporogenesis; climate change; plant infertility; Oryza; temperature; crops, agricultural